Mindfulness, music, visual occlusion in ketamine therapy for depression: do they change outcomes? A qualitative and quantitative analysis of a randomized controlled trial - Kheirkhah, Mina; McDonald, Nastasia; Aepfelbacher, Julia; Rengasamy, Manivel L.; Shivanekar, Sharvari; Spotts, Crystal; Cooper, Iya; Baumeister, Andrew; Bell, Elizabeth; Do-Nguyen, Kevin; Woody, Mary L.; Hossein, Shabnam; et al. (Frontiers in Psychiatry, 2025)
IntroductionThis is the first randomized controlled trial to use both qualitative and quantitative methods to evaluate the effects of a combined sensory intervention that included mindfulness, music, and a light-occluding eye mask during antidepressant-dose ketamine treatment for depression.MethodsForty-three participants with unipolar depressive disorder enrolled in the study; 22 individuals were randomly assigned to receive mindfulness, music, and eye mask during ketamine infusion, and 21 individuals in the control group received only ketamine without additional interventions. Quantitative analyses assessed the impact of combined sensory intervention on ketamine’s antidepressant effects, and qualitative analyses explored the participants’ experiences.ResultsDepression scores improved significantly and similarly across both groups. However, adding combined sensory interventions to ketamine infusion enriched subjective experience. More participants in the combined sensory intervention group reported deeper engagement, a stronger sense of connection to reality, increased focus on the experience rather than the strangeness of it, moments of relief from sadness, and feelings of awe and spiritual insight compared to the control group. Four individuals in the combined sensory intervention group also reported discomfort.DiscussionKetamine’s antidepressant effects remained consistent with or without combined sensory intervention; however, mindfulness, music, and eye mask made the experience more meaningful and emotionally rich for many, though it also introduced discomfort for a few—this outcome might be avoided by making these interventions optional. Given the limited research on combining ketamine with sensory interventions, these results contribute valuable insights and underscore the need for further studies to explore this combined therapeutic approach.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05168735, identifier NCT05168735.